PENANAMAN BIBIT POHON ALBASIA SEBAGAI BENTUK KEPEDULIAN TERHADAP LINGKUNGAN DI DESA CEMPLANG KECAMATAN CIOMAS KABUPATEN SERANG - Amaliah, Siti; Lesmana, Ihwan Satria; Nurholisah, Nurholisah; Sofian, Moch Yordan; Anggraeni, Frischa; Harrin, Umaya Dina Shakina; Nurhakim, Lukman (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Planting trees is an effort to restore, maintain and improve natural conditions so that they can continue to produce and function optimally, either as water regulators or environmental protectors. The implementation method used in this medicinal plant planting training program is divided into three stages. This activity was carried out in several stages to ensure understanding and literacy for the people of Cemplang village so that they had a better understanding of protecting the natural environment. The stages themselves were divided into two, namely: Socialization and planting of Albasia trees in the designated area. Albasia tree seeds themselves have several benefits and also have their own unique characteristics because they are one of the reasons why the Uniba KKM 32 Group chose this tree as a form of concern for the natural environment in Cemplang Village, not only that, the community itself is enthusiastic about planting and also understanding related issues. With this socialization because this can help the public increase their understanding of the concept of protecting the natural environment